2019
DOI: 10.1177/0267659119889777
|View full text |Cite
|
Sign up to set email alerts
|

Aortic cannula orientation and flow impacts embolic trajectories: computational cardiopulmonary bypass

Abstract: Introduction: Emboli events are associated with the aortic cannula insertion and final position in the ascending aorta. However, the impact of subtle changes in aortic cannula movement and flow influencing embolic transport throughout the aortic arch is not well understood. The present study evaluated the aortic cannula’s outflow and orientation effect on emboli entering the aortic branch arteries. Methods: A simplified aortic computational model was anteriorly cannulated in the distal ascending aorta with a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This result demonstrated that the specific flow patterns are different for each cannula location and influenced by the two different cannula tip designs, thus illustrating how the AME pathlines followed the primary flow. 23 Therefore, the flow regime based on the cannula position could play a role in active AME management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result demonstrated that the specific flow patterns are different for each cannula location and influenced by the two different cannula tip designs, thus illustrating how the AME pathlines followed the primary flow. 23 Therefore, the flow regime based on the cannula position could play a role in active AME management.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D aorta model was discretised into a meshed domain with wall inflation layers based on earlier work. 23 The turbulent flow model ( k-ε ) and second-order pressure-flow coupling scheme were adopted for this simulation. The iteration calculations were terminated when the continuity, momentum and turbulence parameter residuals exceeded an order of (10 −5 ) and the mesh convergence had reached an asymptotic range of <5%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The brachiocephalic artery is the first and largest vessel arising from the aortic arch, and it is possible that the flow of blood from the tip of the arterial cannula (a potential source of some emobli) is directed toward this vessel. 20 A study of neurologic deficits after cardiac surgery reported predominant left sided hemiparesis. 21 If this asymmetry is attributed to the distribution of emboli, this could reflect the higher right sided embolic count.…”
Section: Discussionmentioning
confidence: 99%